Alternative genres in information systems research. Issue 3 (1st May 2017) - Avital, Michel; Mathiassen, Lars; Schultze, Ulrike
Abstract: In this special issue, we advocate a critical stance toward the presentational conventions that we – as authors, reviewers, and editors – accept as the academic article genre. We seek to highlight and illustrate the generative capacity and the significant role of genres in the production of knowledge. Furthermore, we wish to encourage Information Systems (IS) scholars to leverage a wider array of alternative genres to present their research in order to develop new insights on subject matters of interest to the IS discipline, as well as expand on how contemporary and emergent phenomena of interest are conceived and studied. Adopting a broad view of alternative genres, we solicited articles that apply unconventional presentational modalities to expand or challenge the prevailing modus operandi of communicating IS scholarship and practice. Six articles survived a rather lengthy and challenging review process. We briefly discuss the nature of the academic article genre and the role of alternative ways of writing. We also introduce the six exemplars of alternative genres in the special issue, namely conversation, French new novel, meditation, memoir, allegory, and crowdsourced research. We highlight key insights and contemplate their implications for current and future IS research.